The Use Of Games In Learning English Grammar - Marcy S. Ferdinandus (Peneliti.net, 2020)
Grammar is perhaps so serious and central in learning another language that all ways should be searched for which will focus student energy on the task of mastering and internalizing it. One way of focusing on this energy through the release offered by games. Miscellany game is a ragbag of useful grammar activities which I find it to classify properly. In this research is carrying out to find out whether or not the miscellany game can be used as a game in the teaching learning process and as a modified technique in increasing students' irregular verbs. In teaching irregular verbs with using game influence standards test 5 % or 1 %. Thus, H1 can acceptable whereas H0 cannot accept.